2007
DOI: 10.1111/j.1524-4733.2007.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Patient Preferences for Colorectal Cancer Screening Using a Choice-Format Survey

Abstract: Our findings emphasize the important role of patient preferences for no screening and in selecting alternative CRC screening modalities. CRC screening implementation in Canada should consider patient preferences to optimize uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 59 publications
(69 reference statements)
13
158
1
1
Order By: Relevance
“…The relationship did not change after controlling for task, country, and demographic characteristics (OR 0.19, 95 % CI 0.14, 0.27; p<0.0001). 11,14 In this study, slightly more than half of respondents selected risk reduction as most important. Those who did not may have perceived the risk of CRC and the reduction in risk as being very small and thus did not consider this attribute to be "important."…”
Section: Intent To Be Screenedmentioning
confidence: 80%
See 1 more Smart Citation
“…The relationship did not change after controlling for task, country, and demographic characteristics (OR 0.19, 95 % CI 0.14, 0.27; p<0.0001). 11,14 In this study, slightly more than half of respondents selected risk reduction as most important. Those who did not may have perceived the risk of CRC and the reduction in risk as being very small and thus did not consider this attribute to be "important."…”
Section: Intent To Be Screenedmentioning
confidence: 80%
“…Some studies have found considerable variation in how people value different attributes, but have not assessed variation across different countries. 11,14,15 By studying the US and Australia, we were able to examine how values and preferences for screening differ in two countries with similar wealth but with differences in how CRC screening has been implemented. US guidelines recommend several options for screening, but implementation has been ad hoc.…”
Section: Introductionmentioning
confidence: 99%
“…24 Although we are not aware of other published studies that have compared different methods of values elicitation for CRC screening, several have used explicit techniques to assess key decisional attributes. 13,[25][26][27][28] (Details of these studies are provided in Appendix 5-available online) Most studies have found test accuracy (ability to detect cancer and polyps) to be the most common most important attribute, but the order of importance of other attributes has varied considerably across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many (including the USPSTF) have argued that providing patients with a choice of mode will increase CRC screening adherence 4,[10][11][12] . This perspective has been challenged by concerns that "information overload" resulting from too many options might lead some patients to opt out of screening altogether 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Extending this assumption to health behavior, if there is variation in preferences regarding the most desirable attributes of a product or service across individuals and these attributes can be varied across products or services, then offering a wide variety of products or services (representing a range of potentially desirable attributes) will be preferable because it will increase the likelihood that each individual will find and act on an option that satisfies his or her unique preferences. Studies comparing preferences for four or more recommended CRC screening options do suggest there is variation in mode preferences and the value patients assign to attributes related to preferences 11,[19][20][21][22][23][24][25] . However, evidence that the vast majority of patients prefer either FOBT or colonoscopy [20][21][22][23]25 calls into question the value of investing in the more rarely preferred screening modalities, particularly in settings where high adherence rates have already been achieved using a screening approach emphasizing a single mode [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%